Den hele bibel i Mynsters og Martensens forkyndelse - Kruse-Blinkenberg, Lars (Kirkehistoriske Samlinger, 1989)
J.P. Mynster (1775-1854) and H. Martensen (1808-1884) occupied a central position in Danish ecclesiastical life in the last century, partly by virtue of the fact that they had each helt the office of Bishop of Zealand in 1834-54 and 1854-1884 respectively. Both had been public figures for a number of years before they were appointed to the bishopric, Mynster from 1810 when his outstanding »Spjellerup sermons« were published, and Martensen from 1838 when he taught at the University of Copenhagen and began to lecture in moral philosophy. Because Mynster’s and Martensen’s homiletic writings are comprehensive, and were at the time very widely read, they are not only of importance to research into Danish 19th-century ecclesiastical history: one cannot even in the 1980s deal with the history of Danish literature of this period without taking their authorship into account, particularly their collected sermons which must as literary sources be considered to rank with the works of, for example, H. C. Ørsted, Hans Christian Andersen, and Søren Kierkegaard. The above treatise examines the way in which Mynster and Martensen employ the Bible in their homilies. Both of them make practical and religious use of the entire Bible, viz. the canonical and apocryphal books of the Old Testament, and the New Testament. The principal aim of the treatise is to try to establish the prominence of the part played by the Apocrypha in the homiletic essays of Mynster and Martensen when these are read as literature. In other words, the Apocrypha as a source not only of the preaching of these two churchmen but of their whole cultural outlook: the use of the Apocrypha in a central Christian context to a high degree imparted to their preaching the harmony and erudition that was linked with Christianity at the beginning and middle of the last century, before the cultural synthesis was broken and cultured theology displaced. The result of the treatise, entitled »Den hele Bibel i Mynsters og Martensens forkyndelse« »The Whole Bible in the preaching of Mynster and Martensen«), is considered in the light of ecclesiastical history. It can be asserted that Mynster’s and Martensen’s application of the Apocrypha is in accordance with the tradition which pre-dates the Reformation; yet it is important to stress that the board biblical view is also Lutheran, and as such, not superseded until the close of the last century by the far more restricted biblical view, and consequently cultural outlook, that still marks Danish religious life: in our time the Apocrypha are reduced to historical source material; the role they play is negligible both in the ministry and in the theological debate. The treatise endeavours to show that the situation today was created about a hundred years ago upon the meeting of popular revivalist movements and historico-critical Bible studies.